Elementary Algebra

Published by Cengage Learning
ISBN 10: 1285194055
ISBN 13: 978-1-28519-405-9

Chapter 11 - Additional Topics - Chapter 11 Review Problem Set - Page 520: 33



Work Step by Step

Using the rule $a^{m}\times a^{n}=a^{m+n}$, we obtain: $3x^{\frac{1}{4}}\times 2x^{\frac{3}{5}}$ $=(3\times2)\times(x^{\frac{1}{4}}\times x^{\frac{3}{5}})$ $=6(x^{\frac{1}{4}+\frac{3}{5}})$ $=6x^{\frac{1(5)+3(4)}{20}}$ $=6x^{\frac{5+12}{20}}$ $=6x^{\frac{17}{20}}$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.